Antibacterial Activity Of Plants Extract Drug Effective Against Pseudomonas aeruginosa Antibiotics Resistance To Quinolone And Cephalosporine: Aktivitas Antibakteri Ekstrak Tanaman Berkhasiat Obat Terhadap Bakteri Pseudomonas aeruginosa Resisten Antibiotik Quinolon Dan Sefalosporin - Kurniawan, Edy; Halid, Idham; Agustina, Agustina (Universitas Muhammadiyah Sidoarjo, 2022)
Antibiotics are empirically used as drugs to treat bacterial infections, but the irrational use of antibiotics causes bacterial resistance to certain antibiotic regimens, therefore solutions are needed to explore alternative drugs. This study aims to explore medicinal plants that are able to inhibit Pseudomonas aeruginosa bacteria that are resistant to quinolones and cephalosporins. The method used is descriptive observational and antibacterial activity test of plant extracts using the well diffusion method. Three plant extracts were used, binahong extract (Andredera cordifolia), tomato fruit extract (Lycopersicon esculentum), and aloe vera extract (Aloe vera). The results showed that only tomato extract inhibited Pseudomonas aeruginosa bacteria with a strong category, while binahong and aloe vera extracts could not inhibit the test bacteria. It was concluded that tomato fruit extract might be an alternative as a medicinal plant because it was able to inhibit P. aeruginosa resistant to quinolones and cephalosporin antibiotics.